Determinants of student performance in an accounting degree programme. Issue 1 (2nd January 2016) - Jansen, Jade; de Villiers, Charl
Abstract : The objective of this study is to identify, by way of regression analysis, the factors that have a significant relationship with student performance in accounting at the third-year level at universities. This study extends the existing literature on student performance in tertiary level accounting programmes. The results can inform the selection process, as well as develop and incorporate appropriate initiatives to enhance the performance of students in these types of programmes. The sample comprises data obtained from students attempting the exit modules in the 2010 and 2011 academic years at the University of the Western Cape. Findings indicate that at the time when students finish high school, their final-year high school grades are significantly related to their performance in the final undergraduate accounting module. Interestingly, their high school mathematics grades appear to be significantly related to passing or failing Accounting 3, but not the percentage achieved in Accounting 3. After their first year, students' Accounting 1 grades are positively and highly significantly related to their performance in Accounting 3. Similarly, after their second year, students' Accounting 2 grades are positively and highly significantly related to their performance in Accounting 3.